Efficacy and toxicities of doxorubicin plus ifosfamide in the second-line treatment of uterine leiomyosarcoma - Niu, Szu-Yun; Sun, Lou; Hsu, Shih-Tien; Hwang, Sheau-Feng; Liu, Chih-Ku; Shih, Yu-Hsiang; Lu, Ting-Fang; Chen, Yen-Fu; Lai, Li-Ching; Chang, Pei-Lun; Lu, Chien-Hsing (Frontiers in Oncology, 2023)
Purpose Uterine leiomyosarcoma is a rare and aggressive tumor known for its drug resistance and metastatic potential. The standard first-line treatment typically involves anthracycline-based chemotherapy or a combination of gemcitabine and docetaxel; however, there is currently no established second-line treatment. Therefore, the aim of this study was to evaluate the efficacy and toxicity of doxorubicin plus ifosfamide as a potential second-line treatment for uterine leiomyosarcoma. Materials and methods This is a retrospective, single-center, single-arm study. We reviewed the tumor registry data from January 2010 to December 2022 and identified patients with uterine leiomyosarcoma who had previously received first-line salvage or adjuvant treatment involving gemcitabine and taxotere, and later experienced tumor recurrence. Patients who met these criteria were included in the study. The primary endpoint was the efficacy of doxorubicin and ifosfamide as a second-line treatment for uterine leiomyosarcoma, as measured by progression-free survival, 1-year overall survival, and response rate. The secondary endpoint was the adverse events associated with this regimen. Results Fifty-two patients were diagnosed with uterine leiomyosarcoma during the study period, nine of whom were included in the data analysis. All patients had previously received gemcitabine-docetaxel as first-line adjuvant therapy, with a median progression-free survival period of 8.4 months. Doxorubicin-ifosfamide was administered as second-line treatment, with a median progression-free survival of 6.0 months (range: 2.7-79.9 months). The clinical benefit rate of the second-line treatment was 66.7%, with a median overall survival of 33.0 months, and a 1-year overall survival rate of 83.3%. Previous reports have shown that the median progression-free survival for second-line treatments using other regimens ranged from 1.4-5.6 months. The most common adverse event was myelosuppression, with five patients requiring granulocyte colony-stimulating factor and one patient requiring a blood transfusion. No patient discontinued treatment due to unmanageable adverse events. Conclusion Use of doxorubicin with ifosfamide may be a promising and reasonable second-line treatment with manageable adverse events for patients with uterine leiomyosarcoma.